Dinamika Sistem Pemilu Masa Transisi di Indonesia - Istiqananda, Widyanur (Ridwan Institute, 2025)
Indonesia is turning its phase from transition towards democratization through general elections since 1999. After three legislative elections in 1999, 2004, and 2009, the country still shows its difficulties in realizing its democratic consolidation. Some facts disclose that the process to find right election has not yet finished in the country. That is why, as the election time comes, discussions on applying the right system still take place, with which Law No.3/1999, Law No. 12/2003, and Law No. 10/2008 have been respectively amended.